IDENTIFIKASI BATUPASIR SEBAGAI AKUIFER DENGAN APLIKASI GEOLISTRIK KONFIGURASI SCHLUMBERGER (STUDI KASUS DI KECAMATAN GABUS KABUPATEN GROBOGAN) - Faizal Ahmad; Sugeng Widada; Agus Setyawan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Gabus Village at Grobogan district are areas those experiencedsevere drought in the dry season. The existence of water sources are not enough for daily needs of the family. Georesistivityis a method to discover groundwater by position of the aquifer as a water storage. The potential difference of georesistivity processed using IPI2win program to determine the value of resistivity of each layer and RockWork15 as 3D modeling. With the correlation of the results of georesistivity and geologic conditions, then we can determine the depth and thickness of groundwater aquifers. Potential aquifers discovered in the Gabus region is a sandstone free aquifer (not pressed) with a value of resistivity is 13.2 Ωm at a depth of 11 meters from the line surface georesistivity interpreted as overburden.Keywords:aquifer, geoeresistivity, schlumberger